Temporal and spatial organization of doctors' computer usage in a UK hospital department. - Martins HMG; Nightingale P; Jones MR (Medical Informatics & the Internet in Medicine, 2005)
This paper describes the use of an application accessible via distributed desktop computing and wireless mobile devices in a specialist department of a UK acute hospital. Data (application logs, in-depth interviews, and ethnographic observation) were simultaneously collected to study doctors' work via this application, when and where they accessed different areas of it, and from what computing devices. These show that the application is widely used, but in significantly different ways over time and space. For example, physicians and surgeons differ in how they use the application and in their choice of mobile or desktop computing. Consultants and junior doctors in the same teams also seem to access different sources of patient information, at different times, and from different locations. Mobile technology was used almost exclusively during the morning by groups of clinicians, predominantly for ward rounds.